Ligation of the Intersphincteric Fistula Tract and Endorectal Advancement Flap for High Perianal Fistulas in Crohn's Disease: A Retrospective Cohort Study. (7th November 2019) - van Praag, Elise M; Stellingwerf, Merel E; van der Bilt, Jarmila D W; Bemelman, Wilhelmus A; Gecse, Krisztina B; Buskens, Christianne J
Abstract: Background and Aims: Ligation of the intersphincteric fistula tract [LIFT] and advancement flap [AF] procedures are well-established, sphincter-preserving procedures for closure of high perianal fistulas. As surgical fistula closure is not commonly offered in Crohn's disease patients, long-term data are limited. This study aims to evaluate outcomes after LIFT and AF in Crohn's high perianal fistulas. Methods: All consecutive Crohn's disease patients ≥18 years old treated with LIFT or AF between January 2007 and February 2018 were included. The primary outcome was clinical healing and secondary outcomes included radiological healing, recurrence, postoperative incontinence and Vaizey Incontinence Score. Results: Forty procedures in 37 patients [LIFT: 19, AF: 21, 35.1% male] were included. A non-significant trend was seen towards higher clinical healing percentages after LIFT compared to AF [89.5% vs 60.0%; p = 0.065]. Overall radiological healing rates were lower for both approaches [LIFT 52.6% and AF 47.6%]. Recurrence rates were comparable: 21.1% and 19.0%, respectively. In AF a trend was seen towards higher clinical healing percentages when treated with anti-tumour necrosis factor/immunomodulators [75.0% vs 37.5%; p = 0.104]. Newly developed postoperative incontinence occurred in 15.8% after LIFT and 21.4% after AF. Interestingly, 47.4% of patients had a postoperatively improved Vaizey Score [LIFT: 52.9% and AF: 42.9%]. The mean Vaizey Score decreased from 6.8 [SD 4.8] preoperatively to 5.3 [SD 5.0] postoperatively [ p = 0.067]. Conclusions: Both LIFT and AF resulted in satisfactory closure rates in Crohn's high perianal fistulas. However, a discrepancy between clinical and radiological healing rates was found. Furthermore, almost half of the patients benefitted from surgical intervention with respect to continence.